2011
DOI: 10.1007/s10551-011-0766-4
|View full text |Cite
|
Sign up to set email alerts
|

The Ethics of Carbon Neutrality: A Critical Examination of Voluntary Carbon Offset Providers

Abstract: Carbon emissions, global warming, offsets, carbon neutrality, ethics, sustainability,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 10 publications
1
55
0
Order By: Relevance
“…However, most of that work is still conceptual or focuses on a single label or single sector. For instance, Raynolds et al (2007) compare governance of five labels in the coffee sector; Silva-Castaneda (2011) examines one scheme for palm oil, which Partzsch (2011) compares with another; Dhanda and Hartman (2011) focus on carbon offset schemes; etc. Blackman and Rivera (2011) is an exception, reviewing studies of the effectiveness of a wider range of eco-labels from the producer's perspective, finding little empirical evidence either way.…”
Section: Assurance Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of that work is still conceptual or focuses on a single label or single sector. For instance, Raynolds et al (2007) compare governance of five labels in the coffee sector; Silva-Castaneda (2011) examines one scheme for palm oil, which Partzsch (2011) compares with another; Dhanda and Hartman (2011) focus on carbon offset schemes; etc. Blackman and Rivera (2011) is an exception, reviewing studies of the effectiveness of a wider range of eco-labels from the producer's perspective, finding little empirical evidence either way.…”
Section: Assurance Practicesmentioning
confidence: 99%
“…Kollmuss et al (2008), cited in Dhanda and Hartman (2011), include third-party verification as a requirement for carbon offset standards to be credible. Various studies have demonstrated that voluntary programs deliver better results if they involve external monitoring: Potoski and Prakash (2005) and Darnall and Kim (2012) in the context of ISO 14001 certification, Graffin and Ward (2010) in the context of Baseball Hall of Fame, or Behnam and MacLean (2011) for international accountability standards.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Voluntary schemes, such as the CDM Gold Standard, have attempted to value the conditions of life around CDM projects and have been profitable for a limited number of CDM market actors (Dhanda and Hartman, 2011). For example, the consultancy firms which verify the additional social and environmental standards benefit from increased business, project developers receive a premium price for their offsets, and the polluting companies that purchase them gain additional marketing benefits beyond simple compliance (Paterson, 2010, page 361).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of waste hierarchy, however, this practice may be near the bottom, as the amount of waste remains stable. Others have critiqued offsetting for its presumed lack of scientific legitimacy stemming from the inherent uncertainty of calculating the carbon footprint of particular activities (such as set building) or the moral complications of discharging environmental duties by pricing carbon [28][29][30].…”
Section: Steps Towards Better Practices In Film and Televisionmentioning
confidence: 99%